APLIKASI TEKNOLOGI PEMBUATAN PUPUK ORGANIK PLUS UNTUK MENINGKATKAN PRODUKTIVITAS GAPOKTAN UMA DESA KABUPATEN - I.G.R.M. temaja; G.N.A.S. Wirya; N.L.G. Sumardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
The short course on organic fertilizer plus was held on Thursday, April 20, 2017 at Simantri 376. There are32 members of Gapoktan Uma Desa participated in this program. The purpose of the short course is toprovide knowledge, understanding and skill to members of Gapoktan about increasing productivity throughthe utilization of bali cattle dung as an organic fertilizer that has higher economic value. The problem solvingmethod is to give theory and practice about formulating fermented organic fertilizer, Trichoderma on carriermedia and organic fertilizer plus. During the delivery of theory and practice the participants' responses werevery enthusiastic, so the discussion took place actively